Pemberdayaan Masyarakat Dalam Pengelolaan Keuangan Dan Investasi Di Kampung Adat Segunung, Desa Carangwulung, Kecamatan Wonosalam, Kabupaten Jombang - Nekky Rahmiyati; Endah Budiarti (LPPM STIKOM Tunas Bangsa, 2021)
This community empowerment program through knowledge of planning and financial management and investment for SMEs and the people of the Segunung Traditional Village aims to teach SMEs and the people of the Gunung Gunung adat, how to make financial planning starting from making budgets, seeking additional funds, making financial reports and invest in business development and also carry out financial planning for the business. The program is implemented in the form of training and assistance in financial management of SMEs and economic actors in the Segunung Traditional Village. The end of this program is expected to show changes in conditions before and after the implementation of the community empowerment program for SMEs and the people of Segunung Traditional Village, namely having more positive attitudes in financial management, and can develop their business.